Histological Changes Resulting From Infection With The Entamoeba Histolytica In Mice And The Effect Of Treatment With Extracts Of The Aloe Barbadensis Plant - Daham, Shahad Saad (Universitas Muhammadiyah Sidaorjo, 2025)
The current study was designed to investigate the effect of aqueous and alcoholic extracts of Aloe barbadensis on the tissues of 4-8-week-old male Balb/c mice weighing 22-28 grams, collected from the beginning of September 2025 until October 2025. These mice were taken from the animal house of the College of Veterinary Medicine, Tikrit University, and placed in special cages in the animal house, which were bedded with wood shavings. Care was taken to keep the cages clean. Microscopic examination of tissue sections taken from mice infected with the Entamoeba histolytica parasite revealed pathological histological changes in the large intestine (colon) and liver. Specifically, necrosis of the intestinal mucosa was observed in the lamina propria, along with degeneration of several cells lining the intestinal glands. Large numbers of white blood cells were also found infiltrating the lamina propria between the glands, compared to the control group. The intestinal glands appeared tubular in shape with cavities containing mucous droplets. Between the bases and walls of the glands, mucous membranes were also found. In the liver of the positive (infected) control group, the portal vein appeared longitudinally wide and contained a mass of red blood cells and some white blood cells, with thickening of its wall adjacent to the bile duct, compared to the negative (uninfected) control group. Microscopic examination of histological sections taken from the intestines of mice infected and treated with an aqueous extract of Aloe barbadensis showed that the intestinal mucosa contained epithelial cells lining the intestinal lumen, with a large number of mucosal goblet cells distributed among the epithelial cells. In the infected liver treated with the aqueous extract, the liver cells appeared in long rows, each row containing normal-shaped hepatocytes with a polygonal appearance and a large, spherical nucleus. In the intestines of mice infected and treated with an alcoholic extract of Aloe barbadensis the intestinal mucosa showed numerous mucosal goblet cells and mucosal droplets in the cytoplasm of these cells, in addition to columnar epithelial cells facing the lumen. In the intestines and in the infected liver treated with the alcoholic extract, the liver tissue contained hepatocytes arranged in interlocking rows similar to honeycomb cells with large spherical nuclei, indicating the efficiency of the extracts in repairing damaged tissues.